Wet combing for head lice: feasibility in mass screening, treatment preference and outcome - Vander Stichele, R H (The Royal Society of Medicine, 2002)
There is no scientific consensus on the best way to control head louse infestation in schoolchildren. A study was conducted to test the feasibility and acceptability of a screening campaign by wet combing and a community approach to head-louse control with home visits, and to explore parents' treatment preferences and treatment outcomes. A non-controlled intervention (advice on treatment options offered to all positive children) was nested within an epidemiological prevalence study. All children in three primary schools in Ghent, Belgium, were invited to take part in screening by wet combing (n=677, 3-11 years). Positive children were offered structural treatment advice, a home visit on day 7, and a check by wet combing on day 14. 83% of the children were screened. The prevalence of active infestation (living moving lice) was 13.0% in school 1 and 19.5% in school 3. In school 2, prevalence of signs of active and past infestation was 40.7%. A home visit was made to 58% of the positive children. 85% of the positive children were screened again on day 14. Wet combing was the most widely used treatment, followed by chemical treatment and a combination of the two. In school 1 and 3 51% were cured, and in school 2 24% became nit-free. A wet combing screening campaign and a community-oriented approach to head-louse control is feasible though resource-intensive. The prevalence of head lice was high and the cure rate was low, with either topical treatments or wet combing.